The effect of perceived organizational fairness on the endogenous motivation of university teachers’ professional development: A study of the mediating role of trust and organizational identification - Yangqin Wang (PLoS ONE, 2025)
Objective The purpose of this study is to investigate the effects of perceived organizational fairness, organizational identity, and trust on the intrinsic motivation for the professional development of university teachers. In addition, this study aims to verify the mediating role of organizational identity and trust. Method This study adopts a quantitative research methodology to investigate the relationship between perceived organizational fairness, organizational identity, trust, and intrinsic motivation in the professional development of university teachers by constructing and validating a structural equation model. Result The study shows that perceived organizational fairness has a significant positive effect on the intrinsic motivation for the professional development of university teachers. Moreover, it validates the mediating effects of organizational identity and trust in the relationship between perceived organizational fairness and intrinsic motivation for teachers’ professional development, shedding light on the psychological mechanisms underlying teachers’ professional development motivation. Conclusion Organizational identity and trust not only directly influence teachers’ intrinsic motivation for professional development but also serve as mediators in the relationship between perceived organizational fairness and intrinsic motivation. These findings have important implications for university management in promoting teachers’ professional development and enhancing educational quality.